The Wiley-Blackwell companion to cultural geography - Johnson, Nuala Christina 1962-; Schein, Richard; Winders, Jamie (Chichester, West Sussex Wiley-Blackwell, 2013)
"A significantly revised new edition of this authoritative reference volume which traces the historical evolution of cultural geography through to the very latest research"--Provided by publisher.
Introduction / Nuala C. Johnson, Richard H. Schein, and Jamie Winders -- Theoretical dispatches -- Foundations -- Landscapes -- Natures/cultures -- Circulations/networks/fixities.
Keywords: Human geography